Occurrence of Some Rare, Endangered and Red Listed Endemic Plants in Velliangiri Hills, a Part of Nilgiri Biosphere Reserve, India - Murugesan, M.; Balasubramaniam, V. (Indian Forester, 2010)
The present paper highlights the occurrence of 31 species of very little known rare, endangered and red listed endemic plants in Velliangiri hills, a part of Nilgiri Biosphere Reserve, the Western Ghats of Coimbatore District, Tamil Nadu, India. These species are ecologically very important since they are strictly endemic and confined only to the hills of southern Western Ghats. Correct nomenclature, family, brief description together with phenological, distributional data, specimen examined and IUCN status are given for each species to facilitate further collection and easy identification.